2006
DOI: 10.1055/s-2005-865751
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Type of Substrate Oxidation During Exercise Between Pre and Post Pubertal Markedly Obese Boys

Abstract: The aim of this study was to investigate, in markedly obese children, the effect of puberty on substrate oxidation during an acute bout of exercise. Two groups of markedly obese boys (7 pre pubertal, 8 post pubertal, matched for adiposity) performed an exercise-test designed for measuring carbohydrate and fat oxidation with indirect calorimetry, and consisting of five six-minute steady-state workloads at 20, 30, 40, 50, and 60 % of the theoretical maximal aerobic power. Fat oxidation (mg . min (-1)) is correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
47
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 25 publications
10
47
1
1
Order By: Relevance
“…The maximal fat oxidation rate (MFO) has been expressed in mg/min (Perez-Martin & Mercier, 2001;Dumortier et al, 2002;Brandou et al, 2003Brandou et al, , 2005Brandou et al, , 2006aBrandou et al, , 2006b), g/min (Achten et al, 2003;Achten & Jeukendrup, 2004;Jeukendrup, 2003), mg/min/kg body weight, mg/min/kg fat free mass, and more recently in mg/min/kg muscle mass (Lavault et al, 2011). Muscle can be evaluated from bioimpedance analysis with a validated equation (Janssen et al, 2000), and expression of MFO in mg/min/kg muscle offers at least two advantages: it helps to delineate the effects of training on muscle mass and on the ability of www.intechopen.com Measurement and Physiological Relevance of the Maximal Lipid Oxidation Rate During Exercise (LIPOXmax) 11 each kg of muscle to burn lipids; it provides an index which has been shown to be predictive of the effects of exercise on weight loss (Lavault et al, 2011) as indicated below.…”
Section: Methodological Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximal fat oxidation rate (MFO) has been expressed in mg/min (Perez-Martin & Mercier, 2001;Dumortier et al, 2002;Brandou et al, 2003Brandou et al, , 2005Brandou et al, , 2006aBrandou et al, , 2006b), g/min (Achten et al, 2003;Achten & Jeukendrup, 2004;Jeukendrup, 2003), mg/min/kg body weight, mg/min/kg fat free mass, and more recently in mg/min/kg muscle mass (Lavault et al, 2011). Muscle can be evaluated from bioimpedance analysis with a validated equation (Janssen et al, 2000), and expression of MFO in mg/min/kg muscle offers at least two advantages: it helps to delineate the effects of training on muscle mass and on the ability of www.intechopen.com Measurement and Physiological Relevance of the Maximal Lipid Oxidation Rate During Exercise (LIPOXmax) 11 each kg of muscle to burn lipids; it provides an index which has been shown to be predictive of the effects of exercise on weight loss (Lavault et al, 2011) as indicated below.…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…previous exercise performed just before the exercise calorimetry MFO slightly increased (Chenevière et al, 2009a) puberty LIPOXmax and MFO are higher in prepubertal children and gradually decrease throughout puberty to reach adult values at the end of puberty (Brandou et al, 2006b;Riddell et al, 2008 ;(Zakrzewski & Tolfrey, 2011b (Friedlander et al, 1998a(Friedlander et al, , 1998bChenevière et al, 2011 ;Brun et al, 2009a ;Zakrzewski & Tolfrey, 2011b .…”
Section: Modifying Factor Effect Referencesmentioning
confidence: 99%
“…The maximal fat oxidation point is considered as a key point of fat metabolism during exercise and has been used for several purposes such as investigating alterations of substrates metabolism with obesity (Brandou et al 2006;Zunquin et al 2006) or targeting individualized intensities of exercise training (Brandou et al 2005). Whereas the expression of the maximal fat oxidation point as heart rate or power output values is preferred for controlling training intensities, it is commonly expressed as a percentage of maximal oxygen consumption ( _ VO 2max ) or a percentage of maximal heart rate in research studies.…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 diabetic patients are characterized by an impaired substrate utilization [1,2]. Using a specific protocol of exercise calorimetry [3][4][5] we have recently reported [6] that the defect in lipid oxidation during exercise in these patients can be described in terms of balance of substrates used for oxidation during exercise as a lower maximal peak of lipid oxidation (LIPOXmax), shifted toward lower exercise intensity levels.…”
Section: Introductionmentioning
confidence: 99%